Leading synchronous virtual teaching sessions. (16th October 2020) - Nunneley, Chloë E.; Fishman, Michael; Sundheim, Kathryn M.; Korus, Rachel E.; Rosen, Robert H.; Streater, Blair A.; O'Donnell, Katherine A.; Newman, Lori R.; Marcus, Carolyn H.
Abstract: While there has been increasing demand for online education over the past decade, social distancing recommendations during the COVID‐19 pandemic have accelerated the transition from the physical to the virtual classroom. Staples of clinical education, such as grand rounds, noon conferences, case conferences and chalk talks, have been abruptly forced to shift into the digital world. There is an immediate need for guidance on synchronous virtual teaching, especially since health professional educators may lack familiarity with the technologies available and theories that guide their use. The following framework can help educators plan, develop and deliver their virtual teaching sessions to optimize student engagement and produce meaningful learning outcomes.